Study of Glycated Hemoglobin and Lipid Profile in Normotensive Type 2 Diabetic Patients (Community Based Medical Journal, 2025)
A cross-sectional study was conducted in the outpatient departments (OPD) of Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between January and June of 2022, to evaluate the diagnostic value of glycated hemoglobin (HbA1c) in predicting diabetic dyslipidemia. A total of 206 normotensive type 2 Diabetes Mellitus patients were selected for the study (141 females and 65 males) and the data were collected through interview in our hospital. Patients’ blood samples were sent for biochemical tests: HbA1c, fasting blood glucose (FBG) and lipid profile. Dyslipidemia was defined according to the National Cholesterol Education Programme (NCEP) Adult Treatment Panel (ATP) III guidelines. The mean age of male and female patients was 64.66±10.99 and 58.53±14.19 years respectively (p7.0% had significantly higher values compared to the patients with HbAlc≤7.0% (p0.05). HbA1c can be utilized as a potential biomarker for anticipating dyslipidemia in type 2 diabetic patients in addition to ensuring glycemic control.  CBMJ 2025 January: Vol. 14 No. 01 P: 122-127